Immunization with matrix-, nucleoprotein and neuraminidase protects against H3N2 influenza challenge in pH1N1 pre-exposed pigs - Eleni Vatzia; Katherine Feest; Adam McNee; Tanuja Manjegowda; B. Veronica Carr; Basudev Paudyal; Tiphany Chrun; Emmanuel A. Maze; Amy Mccarron; Susan Morris; Helen E. Everett; Ronan MacLoughlin; et al. (npj Vaccines, 2023)
Abstract There is an urgent need for influenza vaccines providing broader protection that may decrease the need for annual immunization of the human population. We investigated the efficacy of heterologous prime boost immunization with chimpanzee adenovirus (ChAdOx2) and modified vaccinia Ankara (MVA) vectored vaccines, expressing conserved influenza virus nucleoprotein (NP), matrix protein 1 (M1) and neuraminidase (NA) in H1N1pdm09 pre-exposed pigs. We compared the efficacy of intra-nasal, aerosol and intra-muscular vaccine delivery against H3N2 influenza challenge. Aerosol prime boost immunization induced strong local lung T cell and antibody responses and abrogated viral shedding and lung pathology following H3N2 challenge. In contrast, intramuscular immunization induced powerful systemic responses and weak local lung responses but also abolished lung pathology and reduced viral shedding. These results provide valuable insights into the development of a broadly protective influenza vaccine in a highly relevant large animal model and will inform future vaccine and clinical trial design.